New developements of the fundamental rights theory as challenges for the Constitutional Procesural - Ruiz Miguel, Carlos (2016)
The fundamental rights constitute the core of the present Theory of the Constitution (and of the nowadays Theory of Law) because they are the more implemented section of the Constitution. This has been the source of the increasing interest in the constitutional interpretation and also explains the development of the Constitutional Procedural Law. This is why the evolution of the fundamental rights specially regarding their legal nature and their transnational effects are also subjects developed by the Constitutional Procedural Law  that  has  created  some  tools  as  the responsibility of the State, the establishment of organs for the objective protection of the fundamental rights, the “national margin of appreciation” in international procedures and poses the challenge of how to guarantee the transnational effectiveness of those rights.